Trends in Diabetes Mortality in Urban and Rural China, 1987–2019: A Joinpoint Regression Analysis - Su, Binbin; Wang, Yiran; Dong, Yanhui; Hu, Gang; Xu, Yike; Peng, Xiaobo; Wang, Qianyun; Zheng, Xiaoying (Frontiers in Endocrinology, 2022)
Purpose: Diabetes mellitus is emerging as an epidemic worldwide, and the incidence and prevalence of diabetes have drastically changed in China over the past 30 years, but data are paucity in its mortality rate. This study aimed to analyze the time trends of mortality rates among patients with diabetes in the rural and urban population in China between 1987 and 2019. Methods: The research data comes from China's annual report on national health statistics and the Chinese Health Statistics Yearbook, Age-standardized mortality rates were calculated by using the direct method based on the world standard population from the World Health Organization. Joinpoint regression analysis was employed to estimate the annual percent change and average annual percentage changes of mortality rates from diabetes mellitus. Results: An overall trend for increment in diabetes mortality was observed. The crude mortality rates and age-standardized mortality rates from diabetes for urban and rural residents in China showed a significant increasing trend between 1987 and 2019. The mortality from diabetes in urban areas has been higher than in rural areas for 30 years. However, due to the rapid increase of rural diabetes mortality in the past decade, the gap between the two gradually narrowed. The age-standardized mortality rates of diabetes increased by about 38.5% in urban areas and 254.9% in rural areas over the whole study period. In addition, the age-standardized mortality rate of females from diabetes was higher than that of males, but this pattern began to change in urban areas in 2012. Finally, the age-standardized mortality rates in the elderly population in China is relatively higher with a faster growth rate, especially in rural areas. Conclusion: These results indicate that diabetes has become a significant public health problem in China. Such an effect increases the demand for strategies aimed at the prevention and treatment of diabetes mellitus. In addition to the prevention and intervention of diabetes in high-risk groups, it is also necessary to establish diabetes screening networks to identify patients with mild symptoms. Early detection and timely intervention can effectively reduce the incidence and mortality of diabetes.